Roles of microglial mitophagy in neurological disorders - Liu, Yang; Wang, Miao; Hou, Xiao-Ou; Hu, Li-Fang (Frontiers in Aging Neuroscience, 2022)
Microglia are the resident innate immune cells in the central nervous system (CNS) that serve as the first line innate immunity in response to pathogen invasion, ischemia and other pathological stimuli. Once activated, they rapidly release a variety of inflammatory cytokines and phagocytose pathogens or cell debris (termed neuroinflammation), which is beneficial for maintaining brain homeostasis if appropriately activated. However, excessive or uncontrolled neuroinflammation may damage neurons and exacerbate the pathologies in neurological disorders. Microglia are highly dynamic cells, dependent on energy supply from mitochondria. Moreover, dysfunctional mitochondria can serve as a signaling platform to facilitate innate immune responses in microglia. Mitophagy is a means of clearing damaged or redundant mitochondria, playing a critical role in the quality control of mitochondrial homeostasis and turnover. Mounting evidence has shown that mitophagy not only limits the inflammatory response in microglia but also affects their phagocytosis, whereas mitochondria dysfunction and mitophagy defects are associated with aging and neurological disorders. Therefore, targeting microglial mitophagy is a promising therapeutic strategy for neurological disorders. This article reviews and highlights the role and regulation of mitophagy in microglia in neurological conditions, and the research progress in manipulating microglial mitophagy and future directions in this field are also discussed.